Earnings of university dropouts across Europe - Francesco Berlingieri; Theresa Bolz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This paper investigates relative earnings of individuals leaving tertiary education without a degree across 18 European countries employing survey data on adult workers. We find that, on average, university dropouts earn 8% more than those never enrolling into tertiary education, but 25% less than university graduates. Moreover, university dropouts do not appear to have better employment chances than other upper secondary graduates while they have a significantly lower employment probability than those graduating from tertiary education. We document substantial heterogeneity across countries concerning whether university attendance without completion is rewarded in the labour market. We find some suggestive evidence that university dropouts are less penalised in terms of earnings in countries with a lower share of tertiary graduates and with more flexible labour market policies.
Keywords: I23; I26; J31; 330; university dropout; returns to higher education; international comparisons